Pemahaman dan Kesiapan Pustakawan terhadap Pemanfaatan Alat Klasifikasi di Era Digital - Novita Dwi Anawati; Indah Rachma Cahyani; Ani Sistarina (Media Pustakawan, 2022)
Cataloging and classification is a major factor in the process of retrieval of information sources. Implementation of cataloging and classification requires reliable librarian competence. In this digital era, librarians are given many choices. Each librarian has strategy in carrying out classification activities, but still adhere to the principle of consistency and ease in the retrieval process. This study aims to provide an overview of the understanding and readiness of academic librarians in East Java state universities for classification tools in the digital era; as well as to know what classification tools are used by academic librarians of public universities in East Java in help their duties. The primary research data were obtained from interviews with 8 librarians in the classification section of East Java state university libraries, namely UNAIR, ITS, UNESA, UPN, UB, UM, UNEJ, and UTM. The method used descriptive qualitative approach. The results of the study show that most of the informants understand the existence of classification tools in the digital era. They know and implement these tools in their work. Most of the informants used the printed DDC as a classification tool in this era, even though they aware of online or digital classification tools. The printed DDC is believed to be reliable and trusted classification tool. Even so, there were informants who knew and understood the existence of a classification tool, but didn’t use it for reasons of inadequate supporting facilities. Most of the informants felt helped by the classification tools in online or digital form.